Candida spp. Determination and Th1/Th2 Mixed Cytokine Profile in Oral Samples From HIV+ Patients With Chronic Periodontitis - Lomeli-Martinez, Sarah M.; Valentin-Goméz, Eulogio; Varela-Hernández, Juan J.; Alvarez-Zavala, Monserrat; Sanchez-Reyes, Karina; Ramos-Solano, Moises; Cabrera-Silva, Rodolfo I.; Ramirez-Anguiano, Victor M.; Lomeli-Martinez, Manuel A.; Martinez-Salazar, Silvia Y.; González-Hernández, Luz A.; Andrade-Villanueva, Jaime F. (Frontiers in Immunology, 2019)
BACKGROUND: Chronic periodontitis (CP), caused by bacteria and fungi, appears in up to 66% of HIV-patients. The impact and association of HIV-treatment (HAART) and Candida itself has not been properly evaluated in the development and progression of CP. The immunopathogenesis is characterized by CD4+ T-cells activation and the balance between the T-helper 1 (Th1) and T-helper 2 (Th2) or a mixed cytokine profile. Currently, the associated causes of an immune response in HIV-patients with CP is controversial. Our aims were the determination of Candida spp. and cytokine profile in oral samples from HIV-positive patients with CP, considering the CD4+ T cells levels and HAART use. METHODS: From 500 HIV-positive patients evaluated, 228 patients were enrolled. Patients were separated in groups: A) n=53 (≤200 CD4+ T-cells on HAART); B) n=57 (≤200 CD4+ T-cells without HAART); C) n=50 (>200 CD4+ T-cells without HAART); D) n=68 (>200 CD4+ T-cells on HAART). Candida spp. were isolated from the oral biofilm and crevicular fluid in CHROMagar and confirmed by endpoint PCR. Cytokine levels were measured by beads-based immunoassay in saliva by flow cytometry. RESULTS: 147 patients (64.5%) were positive to Candida spp. and 204 strains were isolated; 138 (67.6%) were C. albicans and the remaining C. non-albicans species (C. glabrata>C. tropicalis>C. krusei>C. dubliniensis). In this study, CHROMagar showed good sensitivity (95%) but poor specificity (68%); since of the 152 samples identified as C. albicans, only 131 were confirmed by PCR; from the 10 samples identified as C. glabrata, only 6 were confirmed. Finally, of the 42 samples detected as C. tropicalis, only 5 were confirmed. When evaluating Candida spp. presence, group A and D had a higher isolation, while group B had the highest species diversity. Whereas group C had a significant reduction of Candida spp. Despite the presence of Candida and HAART, we found a Th1/Th2 hybrid profile in the saliva of patients with low CD4+ T-cell count (group A). CONCLUSION: Abundance and diversity of the Candida spp. detected in HIV-patients with CP could be related to HAART and low CD4+ T-cells levels. Also, the immunosuppression might promote a local Th1/Th2 hybrid cytokine profile.